Advances in Diagnosis and Therapy of Neuroendocrine Neoplasms (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is dedicated to neuroendocrine neoplasms (NENs), a category of malignancy that demonstrates wide clinical heterogeneity, posing major challenges in diagnosis and management. There have been significant advances in the field of NEN genomics, pathology, imaging, and treatment over the past five years. NENs are examples of rare tumours (although their incidence and prevalence are increasing) where international collaborative efforts have allowed the generation of high-level evidence to guide optimal patient-centred care. This issue presents both reviews and original papers to provide comprehensive state-of-the-art understanding of this fascinating disease.